2022
DOI: 10.1111/iji.12585
|View full text |Cite
|
Sign up to set email alerts
|

VDR gene polymorphisms are associated with the increased susceptibility to COVID‐19 among iranian population: A case‐control study

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), but the pathogenesis is unclear. Host genetic background is one of the main factors influencing the patients' susceptibility to several viral infectious diseases. This study aimed to investigate the association between host genetic polymorphisms of two genes, including vitamin D receptor (VDR) and vitamin D binding protein (DBP), and susceptibility to COVID-19 in a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Apaydin et al indicated that most participants who were admitted to the intensive care unit (ICU) had the TT genotype for TaqI rs731236 polymorphism, whereas the TC genotype was more common in the non-ICU–admitted groups [ 20 ]. In addition, two studies in Iran did not report any relationship between this polymorphism and the COVID-19 mortality rate [ 27 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apaydin et al indicated that most participants who were admitted to the intensive care unit (ICU) had the TT genotype for TaqI rs731236 polymorphism, whereas the TC genotype was more common in the non-ICU–admitted groups [ 20 ]. In addition, two studies in Iran did not report any relationship between this polymorphism and the COVID-19 mortality rate [ 27 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, VDR gene SNPs are considered potentially significant in the study of COVID-19 [ 70 ]. Currently, there are several publications considering rs2228570 as a factor influencing the susceptibility, clinical symptoms and severity of COVID-19, but their number is small [ 33 , 40 , 41 , 42 ]. Abdollahzadeh et al revealed the association of SNP rs2228570 (FokI) with fever and arterial hypertension in severe/critical patients [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CT (heterozygous) genotype has been significantly associated with increased likelihood of COVID-19 compared to CC (homozygous reference standard). In addition, the T allele is also associated with a high susceptibility to SARS-CoV-2 infection [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…
Dear Editor, we would like to share ideas on the publication 'VDR gene polymorphisms are associated with the increased susceptibility to COVID-19 among Iranian population: A case-control study' (Jafarpoor et al, 2022). Jafarpoor et al discovered that a VDR polymorphism (rs2228570) may impact individual susceptibility to COVID-19.
…”
mentioning
confidence: 99%